Exploring Psychological Well-Being Among Tahfiz Al-Quran Students: Emprical Study Using Psychoeducation Counseling and Therapy - Syed Mohd Akhirudin Syed Yahya; Abu Yazid Abu Bakar; Ku Suhaila Ku Johari (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2022)
This study aims to explore mental stress, self-efficacy and coping strategies that contribute to the stability of tahfiz students' mental health. This study is a qualitative study that uses phenomenological methods in psychoeducational group counseling. The respondents of this study consisted of 5 students of Tahfiz School and Malaysian Armed Forces Orphans (STAY ATM) who were 17 years old. Data analysis using content analysis techniques. The results of the study found that the mental stress faced by tahfiz students is caused by parental coercion, military- lifestyle and environmental factors. As a result of the mental stress experienced, emotional changes also occur. In the aspect of self-efficacy, tahfiz students have personal advantages such as being talented in various fields, extroverted, and independent, but their introvert attitude, low self-esteem and not knowing how to manage time are also their weaknesses. From the aspect of coping strategies, tahfiz students have a mature and rational coping strategy in managing the mental stress they face and have a clear future plan. Al Quran approach clearly shows that it can have a positive effect on the mental stability of tahfiz students. The results of this study have positive implications for students, parents, STAY ATM’s and community.